Genetic diversity of Parkia pendula (Willd.) Benth. Ex Walp. native in Amazonia Matogrossense (Research, Society and Development, 2021)
This study aimed to estimate the genetic divergence between Parkia pendula (Will.) Benth. Ex Walp. native in the Amazon of Mato Grosso, based on the physiological characteristics of the seeds. To characterize the seed, the Germination Test, Germination Speed Index, Electrical Conductivity Test and Accelerated Aging Test in a completely randomized design with four replications of 25 seeds were used. To perform the germination test, the seeds were subjected to a procedure to overcome dormancy, where the seeds were immersed in 98% sulfuric acid for 30 minutes. Through the method of grouping the averages, it was found that matrix 15 presented the highest values for germination speed index (19, 20) and percentage of germination (100%). The seeds submitted to the accelerated aging test, presented the best results for germination speed index in matrices 1, 3, 4, 7, 10, 18, 24, 27, 29 and 30 and matrices 2, 4, 6, 7, 8, 9, 10, 12, 15, 16, 17, 18, 20, 21, 24, 26, 28 and 30 with the highest germination percentages. By the Tocher optimization method, six distinct groups were formed and in the dendrogram there was a distinction of V groups. It is concluded based on the population studied that there was great genetic diversity for attributes related to seed morphophysiological characteristics.